Answer :

Given: … (1)


ax - by = 2ab … (2)


Multiplying by ab to (1) and a to (2), we get


a2x – b2y = a2b + ab2 … (3)


a2x – aby = 2a2b … (4)


Subtracting equation (4) from equation (3),


(a2x – a2x) + ( - aby) – ( - b2y) = (2a2b - a2b) – ab2


- aby + b2y = a2b – ab2


by(b – a) = ab(a – b)


y = b(b a) / ab(a b)


y = - a


Substitute y value in (2),


ax – b( - a) = 2ab


ax + ab = 2ab


ax = ab


x = b


The solution is x = b and y = - a.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics